THE STRUCTURE OF ROMANTICISM IN INDONESIAN POETRIES - Samsuddin Samsuddin (Universitas Sembilanbelas November Kolaka, 2016)
Romanticism is a growing understanding in the literature which is operationally working on two things, namely the ideal world and the factual world. Considers that the ideal world of ideas, thoughts and ideas stems from gaps in life both personally and socially. Everything is present in an ideal world is always seen as something that is good in law, law, customs and religiously. Unlike the case with factual world. Factual world sometimes is not always in line with the ideal world. In these conditions there was a clash between the world of ideas and factual. In this condition the condition of poetry is always present to neutralize the gap between the ideal and the factual world. Poetry exists to provide a description, breaking up, providing a solution to the existing gaps. Poetry poet anxiety stems from the gap that occurs both personally and socially. Poetry comes to identify study and modify the gap into a road that can be taken and considered to ward off the gap. Although in all facets of life can be engineered factual world, but in particular the idea kataristik as a form of purification can occur through poetry.Poetry Surat Cinta by Mashun comes from the gap that occurs in the poet. The gap that occurs in some aspects that can be traced through nature, the elements and means poetry. One of them can be traced to the choice of words like love letters and hardback dusk. The word choice is the romance is the opposition. A love letter is an expectation that spans a row of stories carved out by two people who complement each other, complementary and understanding between the two. However, they do not walk in a straight line, for the love letters carved turns both hardback dusk, an illustration that will soon be arriving the night. A horizon that is beautiful to look at. However, the beauty of the horizon with violet color does not last long because the night soon engulfed everything. Opposition two things are done and poet strongly opposed to the whole poem.